2015
DOI: 10.1586/17476348.2015.1103649
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric analysis of the top 50 cited respiratory articles

Abstract: A periodic evaluation of the top cited articles can help researchers identify the quality of work in respiratory system and pinpoint subtopics which have not been given due consideration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 16 publications
0
36
0
2
Order By: Relevance
“…Some of our findings are similar to those reported in other scientific topics, particularly that the United States dominates world scientific production. [8][9][10][11][12][13][14] As in other citation analyses, several shortcomings need to be addressed in the current study. First, the exclusive use of pleural effusion as the search parameter may have resulted in the overlooking of some articles which employed other key terms (eg, empyema, pleurodesis, thoracentesis, etc).…”
Section: Discussionmentioning
confidence: 99%
“…Some of our findings are similar to those reported in other scientific topics, particularly that the United States dominates world scientific production. [8][9][10][11][12][13][14] As in other citation analyses, several shortcomings need to be addressed in the current study. First, the exclusive use of pleural effusion as the search parameter may have resulted in the overlooking of some articles which employed other key terms (eg, empyema, pleurodesis, thoracentesis, etc).…”
Section: Discussionmentioning
confidence: 99%
“…Although it is unwise to assess the quality of a study based only on its citation rating, the frequency of citing has significant implications for authors, journals, institutions and even countries, as it is one of the markers of the impact of an individual scholarly work within the scientific community [1]. Therefore, various techniques have been used to identify the most frequently cited articles in both medical and surgical specialties, including traumatic brain injury [2], neurosurgery [3], orthopedics [4], cardiac surgery [5], urology [6], cardiovascular disease [7], hypertension [8], and lung disease [9]. …”
Section: Introductionmentioning
confidence: 99%
“…Several papers have reported analyses of the most‐cited publications in a number of fields of health sciences, including dentistry, where different specialties have also been separately addressed …”
Section: Introductionmentioning
confidence: 99%
“…3 Moreover, Callaham et al concluded that the strongest predictor for the number of obtained citations in a paper is the journal impact factor, meaning that the publishing journal could be considered important in the evaluation of the quality of a publication. 4 Several papers have reported analyses of the most-cited publications in a number of fields of health sciences, [5][6][7][8][9] including dentistry, where different specialties have also been separately addressed. [10][11][12] The aim of the present study was to identify, after interrogating two distinct electronic databases, the 100 most-cited articles in the field of periodontology and to provide a descriptive analysis of the results.…”
Section: Introductionmentioning
confidence: 99%